The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.3354/dao036061
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic castration in Concholepas concholepas (Gastropoda:Muricidae) due to a larval digenean in northern Chile

Abstract: Specimens of the edtble mollusk Concholepas concholepas from Tocopllla northern Chile, were found to b e Infected with larval forms of a fellodislom~d d~g e n e a n Plevalence of infection did not signlflcantly differ between male and female mollusks A close ielat~onshlp between first maturlty and parasitic infection is suggested Flukes invade gonadal and hepatopancreat~c tlssue and adversely affect structure and functlon of these organs In heavy infections the penls was absent and destruction of the hepatopan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In the freshwater semelparous clam Pisidium amnicum, 3 digenean parasite species castrated their hosts and no clams containing parasites and embryos were found, semelparity being produced by the parasites (Rantanen et al 1998). Also in the gastropods Concholepas concholepas (Oliva et al 1999) and Ilyanassa obsoleta (Sullivan et al 1985), castration by Digenea have been described as a decrease in the sizes of the acini and of the gonad, although no information was obtained on the effects on the germ cell line. Pressure exerted by the growing 155 (Reader 1973).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the freshwater semelparous clam Pisidium amnicum, 3 digenean parasite species castrated their hosts and no clams containing parasites and embryos were found, semelparity being produced by the parasites (Rantanen et al 1998). Also in the gastropods Concholepas concholepas (Oliva et al 1999) and Ilyanassa obsoleta (Sullivan et al 1985), castration by Digenea have been described as a decrease in the sizes of the acini and of the gonad, although no information was obtained on the effects on the germ cell line. Pressure exerted by the growing 155 (Reader 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Sporocysts of this trematode occur within reproductive tissues, where they cause parasitic castration, a condition defined as a total or partial reduction in gamete production (Sullivan et al 1985, Emerson-Kagoo & Ayyakkannu 1994. While this phenomenon has been observed in several species of bivalves (Feng 1988, Cousteau et al 1990, Jonsson & André 1992, Lasiak 1991, Santos & Coimbra 1995, Calvo-Ugarteburu & McQuaid 1998, Rantanen et al 1998, Silva et al 2002 and gastropods (Reader 1973, Sullivan et al 1985, Oliva 1992, Oliva et al 1999, the extent of the gonadal damage has not been measured at the histological level. Although the bivalve mytilid Perna perna when parasitized by bucephalid trematodes has marked reduction in reproductive tissue (Silva et al 2002), no quantitative information about the damage at the germ cell line level is available.…”
Section: Introductionmentioning
confidence: 99%
“…In South America, studies of parasites and diseases of bivalves are scarce (CaceresMartinez & Vasquez-Yeomans 2008), even though they are important and necessary. In Chile, major contribution about presence of parasites in molluscs have been recorded by Oliva (1984Oliva ( , 1992, Oliva et al (1986Oliva et al ( , 1999Oliva et al ( , 2010, Franjola & Gallardo (1991), Gallardo et al (1992), Oliva & Vega (1994), García-Tello et al (2002), Valderrama et al (2004), and pathogens by Lohrmann et al (2002), Lohrmann (2009), Campalans & Lohrmann (2009. However, the knowledge of pathogens and parasites in marine organisms inhabiting San Jorge Bay (Antofagasta) and the majority of the Chilean coast remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, prevalence and number of parasites per host were related to the size of the bivalves because larger surfaces provide more area for colonization (Cáceres-Martínez et al, 1999). Oliva et al (1999) reported that the proportion of infested mollusks increased with the size of the host in Concholepas concholepas. Cáceres-Martínez et al (1996), studying specimens of M. galloprovincialis from a polluted environment, found the prevalence of P. spinosus in this species reached 100% (up to 59 parasites per mussel).…”
Section: Discussionmentioning
confidence: 99%